Arrhythmogenic right ventricular cardiomyopathy (ARVC) mimics: the knot unravelled by cardiovascular MRI. Issue 3 (March 2019) - Amadu, A.M.; Baritussio, A.; Dastidar, A.G.; De Garate, E.; Rodrigues, J.C.L.; Biglino, G.; Lyen, S.; Diab, I.; Duncan, E.; Nisbet, A.; Thomas, G.; Angelini, G.D.; et al.
Abstract : AIM: To assess the role of cardiovascular magnetic resonance imaging (CMRI) in patients referred for suspected arrhythmogenic right ventricular cardiomyopathy (ARVC), its ability to identify ARVC mimics, and subsequent clinical impact. MATERIALS AND METHODS: The CMRI registry of the year 2014 was analysed to identify all consecutive patients referred for suspected ARVC. A comprehensive CMRI protocol that included anatomy, bi-ventricular function modules, and late gadolinium enhancement (LGE) was performed in all patients. RESULTS: Out of 2, 481 CMRI performed, 124 patients (5%) were referred for suspected ARVC. A pathological substrate was identified at CMRI in 36 patients (29%): five patients (4%) had ischaemic heart disease (IHD) and 10 (8%) non-IHD; five patients (4%) met CMRI criteria for ARVC and 16 (13%) were ARVC mimics. right ventricular end-diastolic volume (RVEDV) and right ventricular stroke volume (RVSV) were significantly higher in patients with ARVC mimics (RVEDV p= 0.007, RVSV p= 0.012) and ARVC (RVEDV p= 0.013, RVSV p= 0.013), as compared to those with structurally normal hearts. CMRI was superior to echocardiography in the identification of ARVC mimics (13% versus 1%, p= 0.01). CONCLUSIONS: CMRI was able to identify 16 (13%) ARVC mimics, from congenital abnormalities to acquired heart disease. CMRI was superior in identifying ARVC mimics compared to echocardiography, and overall provided a change in diagnosis in 22% of patients. Highlights: Patients meeting CMR criteria for ARVC represent (4%) of patients referred for suspected ARVC. ARVC mimics are not an uncommon finding (13%) among patients referred to CMR for suspected ARVC. Not all ARVC mimics are normal variants, as pathological conditions are also encountered. CMR shows to be superior to trans-thoracic echocardiogram in the detection of ARVC mimics (p=0.01).